â€œCONCEPT OF AGNI AND ITS ROLE IN THE PATHOGENESIS OF AMLAPITTA VYADHI : A REVIEW â€: Array - Dr. Anuja Katkhede (Ayurline: International Journal of Research in Indian Medicine, 2021)
The ancient system of Indian medical science Ayurveda describes various concepts related to physiological functioning and biological response. Agni is considered responsible for the digestive & metabolic functioning of the body. The digestion & assimilation of ingested food performed by the Agni which is very essential process for the growth and development of human body. Ayurveda emphasizes that all the diseases are the result of the weak state of Agni i.e. Mandagni. Improper functioning of Agni leads to various gastrointestinal disorders as well as various metabolic disturbances. Agni offers Arogya, Ayu, Bala, Swasthyam, Varnam, Utsaha, Ojha, Prabha,& Teja to the body which all resembles a healthy physical and mental state. Agni Dusthi is one of the causative factors for many diseases, therefore, Agni play important role towards understanding of disease pathogenesis, disease diagnosis, & setting of the treatment protocol. Amlapitta is a disease which is commonly found in almost all parts of the world. Peculiarities of this disease are, increased prevalence, vast field of manifestation of symptoms, requires prolonged dietetic control, if not treated in proper time, it may create major problems. Amlapitta is one of the commonest Vyadhi of Annavaha Strotas, caused by vitiated Agni. Amlapitta is a condition where Amla Guna of Pachak Pitta increases due to Samata. The main principle of treatment of all diseases as per Ayurveda is to restore and to strengthen the Agni. This article emphasized the conceptual understanding of Agni & its role in the pathogenesis of Amlapitta Vyadhi.